Cautionary notes on the use of NF-κB p65 and p50 antibodies for CNS studies - Herkenham, Miles (BioMed Central, 2011)
BACKGROUND: The characterization and cellular localization of transcription factors like NF-κB requires the use of antibodies for western blots and immunohistochemistry. However, if target protein levels are low and the antibodies not well characterized, false positive data can result. In studies of NF-κB activity in the CNS, antibodies detecting NF-κB proteins have been used to support the finding that NF-κB is constitutively active in neurons, and activity levels are further increased by neurotoxic treatments, glutamate stimulation, or elevated synaptic activity. The specificity of the antibodies used was analyzed in this study. METHODS: Selectivity and nonselectivity of commonly used commercial and non-commercial p50 and p65 antibodies were demonstrated in western blot assays conducted in tissues from mutant gene knockout mice lacking the target proteins. RESULTS: A few antibodies for p50 and p65 each mark a single band at the appropriate molecular weight in gels containing proteins from wildtype tissue, and this band is absent in proteins from knockout tissues. Several antibodies mark proteins that are present in knockout tissues, indicating that they are nonspecific. These include antibodies raised against the peptide sequence containing the nuclear localization signals of p65 (MAB3026; Chemicon) and p50 (sc-114; Santa Cruz). Some antibodies that recognize target proteins at the correct molecular weight still fail in western blot analysis because they also mark additional proteins and inconsistently so. We show that the criterion for validation by use of blocking peptides can still fail the test of specificity, as demonstrated for several antibodies raised against p65 phosphorylated at serine 276. Finally, even antibodies that show specificity in western blots produce nonspecific neuronal staining by immunohistochemistry. CONCLUSIONS: We note that many of the findings in the literature about neuronal NF-κB are based on data garnered with antibodies that are not selective for the NF-κB subunit proteins p65 and p50. The data urge caution in interpreting studies of neuronal NF-κB activity in the brain.